Modulation of a ligand's energy landscape and kinetics by the chemical environment - Held, Martin; Imhof, Petra; Keller, Bettina G.; Noe, Frank (Journal of Physical Chemistry B, 2012)
Understanding how the chemical environment modulates the predominant conformations and kinetics of flexible molecules is a core interest of biochemistry and a prerequisite for the rational design of synthetic catalysts. This study combines molecular dynamics simulation and Markov state models (MSMs) to a systematic computational strategy for investigating the effect of the chemical environment of a molecule on its conformations and kinetics. MSMs allow quantities to be computed that are otherwise difficult to access, such as the metastable sets, their free energies, and the relaxation time scales related to the rare transitions between metastable states. Additionally, MSMs are useful to identify observables that may act as sensors for the conformational or binding state of the molecule, thus guiding the design of experiments. In the present study, the conformation dynamics of UDP-GlcNAc are studied in vacuum, water, water + Mg2+, and in the protein UDP-GlcNAc 2-epimerase. It is found that addition of Mg2+ significantly affects the conformational stability, thermodynamics, and kinetics of UDP-GlcNAc. In particular, the slowest structural process, puckering of the GlcNAc sugar, depends on the overall conformation of UDP-GlcNAc and may thus act as a sensor of whether Mg2+ is bound or not. Interestingly, transferring the molecule from vacuum to water makes the protein-binding conformations UDP-GlcNAc first accessible, while adding Mg2+ further stabilizes them by specifically associating to binding-competent conformations. While Mg2+ is not cocrystallized in the UDP-GlcNAc 2-epimerase complex, the selectively stabilized Mg2+/UDP-GlcNAc complex may be a template for the bound state, and Mg2+ may accompany the binding-competent ligand conformation to the binding pocket. This serves as a possible explanation of the enhanced epimerization rate in the presence of Mg2+. This role of Mg 2+ has previously not been described and opens the question whether "binding co-factors" may be a concept of general relevance for protein-ligand binding. © 2012 American Chemical Society.
CRIS-Team Scopus Importer:2020-02-18